Profesionalisme Guru Sekolah Menengah Pertama Negeri 13 Bintan - mandala, edward; Arfa, Desmayeti; Sujono, Agus; Sulistiani, Dewi (STISIPOL Raja Haji, 2022)
Professionalism is an attitude and behavior that must be possessed as an educator. Teachers are the most decisive driving force in the education system as a whole, and as an implementation of the recognition In accordance with the requirements that must be met, it is stated in Law No. 14 of 2005 concerning Teachers and Lecturers. Teachers and Lecturers are required to have academic qualifications, educator certificates, physically and mentally healthy, and have the ability to make it happen. This research was conducted to find out the extent to which the professionalism of the SMP Negeri 13 Bintan teachers towards the students at the State Junior High School 13 Bintan. Based on the concept of Ace Suryadi (Trisoni 2011). By looking at the four characteristics of professional teachers namely, Professional Capacity, Professional Effort, Time Devotion, Professional rent, while the population and sample are 8 people consisting of teachers certified and uncertified at the State Junior High School 13 Bintan as key informants. The method in this research is using descriptive qualitative. Data collection techniques using observation, interviews and documentation. His tools are interview guides and checklists.The results of this study indicate that the professionalism of the teachers of the 13 Bintan State Junior High Schools has been going well, the skills and attitudes of the teachers required have met the standards. While the suggestions in this study are expected that teachers can improve teacher professionalism by continuing tomake improvements and attend trainings that can add insight and professional Knowledge.